ENT300: Case Study Assessment (PG Arena Sdn. Bhd.) / Muhamad Zubair Mad Sam...[et al.] - Mad Sam, Muhamad Zubair; Yahaya, Deena Ashikin; Ramli, Nur Dalila; Baharudin, Nurul Farhanim; Md Saad, Norarifah (2020)
The PG Arena was founded in 2016 and operated in online business. In 2018, it was incorporated the sportswear store in Kedah under the name PG Arena Sdn. Bhd. It is partnership business that shared by Kedah’s footballers, Rafiz bin Abu Bakar,Ahmad Fauzi bin Saari (Paklong) and Baddrol bin Bakhtiar. Unfortunately, Paklong is backing out because he’s busy on his schedule.